Investigating Cryptocurrencies - Furneaux, Nick (Ascent Audio, 2019)
Investigate crimes involving cryptocurrencies and other blockchain technologies Bitcoin has traditionally been the payment system of choice for a criminal trading on the Dark Web, and now many other blockchain cryptocurrencies are entering the mainstream as traders are accepting them from low-end investors putting their money into the market. Worse still, the blockchain can even be used to hide information and covert messaging, unknown to most investigators. Investigating Cryptocurrencies is the first book to help corporate, law enforcement, and other investigators understand the technical concepts and the techniques for investigating crimes utilizing the blockchain and related digital currencies such as Bitcoin and Ethereum. Listen to this book to: understand blockchain and transaction technologies, set up and run cryptocurrency accounts, identify users of cryptocurrencies, and more. With nearly $150 billion in cryptocurrency circulating and $3 billion changing hands daily, crimes committed with or paid for with digital cash are a serious business. Luckily, Investigating Cryptocurrencies shows you how to detect it and, more importantly, stop it in its tracks.